Intestinal Microbiota and Sclerosis Lateral Amyotrophic - Mariana Dantas de Carvalho Vilar; Sancha Helena de Lima Vale; Eliane Lopes Rosado; Mário Emílio Teixeira Dourado Júnior; José Brandão-Neto; Lúcia Leite-Lais (Hospital de Clínicas de Itajubá, 2022)
The human gastrointestinal tract contains numerous microorganisms. This intestinal microbiota (IM) has a mutualistic relationship with the human organism, and it plays a fundamental role in regulating metabolic, endocrine, and immunological functions. Intestinal dysbiosis is associated with phenotypes of many chronic and inflammatory diseases. This association is explained by the functions of the IM and the existing bi-directional communication of the microbiota-intestine-brain axis. Studies have uncovered new evidence between the IM and neurodegenerative diseases recently, including amyotrophic lateral sclerosis (ALS). Given this, the present narrative review discusses didactically about IM, its functions, its relationship with the neuroimmune-endocrine system, and its association with neurodegenerative diseases, with emphasis on ALS.